Peran Organisasi Masyarakat (Ormas) dan Lembaga Swadaya Masyarat (LSM) dalam Pembangunan Berkelanjutan di Indonesia - Abdul Rahman; Sadu Wasistiono; Ondo Riyani; Irwan Tahir (Ekonomis: Journal of Economics and Business, 2023)
This research discusses the crucial role played by Community Organizations and Non-Governmental Organizations in efforts to achieve sustainable development in Indonesia. Sustainable development is the main goal that has received serious attention from various countries, including Indonesia. These development goals pursue an important balance between economic growth, environmental sustainability, and community empowerment. The method used is a qualitative approach involving field surveys, interviews and document analysis. interact directly with leaders of Community Organizations and Non-Governmental Organizations during field surveys. This method is used to gain a deeper understanding of the role of Community Organizations and Non-Governmental Organizations in varied local contexts and provide a holistic view of their contribution to Indonesia's development. The research results show that Community Organizations and Non-Governmental Organizations have great potential in mobilizing the community, advocating for better policies, and providing necessary services for community members. However, there are challenges that need to be overcome, including financial issues, organizational capacity, and relations with government, several empowerment strategies that can be used to strengthen the role of Community Organizations and Non-Governmental Organizations in the development process, including increasing organizational capacity, promoting partnerships with the sector private sector, and strengthening inter-organizational networks. This research provides a deeper understanding of how Community Organizations and Non-Governmental Organizations can contribute more effectively in supporting sustainable development in Indonesia.